DISTRIBUTION OF FIRE INCIDENTS AND FIRE FIGHTING SERVICES IN DKI JAKARTA PROVINCE - Zakaria, Muhammad; Tambunan, Mangapul P.; Setiadi, Hafid (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2023)
The rapid development of the city results in the risk of disasters, one of which is a fire disaster. Fire incidents have increased from time to time, this occurs in line with the continued increase in population and density of settlements. Fire can cause material loss or loss of life. Efforts to minimize fire disasters can be carried out by providing fire fighting service facilities whose numbers can reach all areas. The purpose of this study is to determine the distribution of fire incidents and to determine the distribution of fire services in DKI Jakarta Province. The type of research used in this research is ex-post facto research which then the results are analyzed by quantitative description. The location of this research is DKI Jakarta Province. The variables in this study are fire incidents and fire fighting services in the 2018-2020 range. The source of data in this study is data on fire incidents and fire fighting services obtained from related agencies, namely the DKI Jakarta Fire Department. Data analysis techniques are density analysis and service area analysis. The results showed that the distribution of fire incidents occurred in all areas of DKI Jakarta, with the highest distribution in the East Jakarta area. The spread of fires occurred in almost every residential or residential area. The distribution of fire services in DKI Jakarta is not available in every region, especially at the sub-district and urban village levels. Keywords: Fire, fire fighter, fire sector, fire station, housing, settlement